Soil macrofauna communities and cover crops in a Cerrado Oxisol under no tillage - Santos, Glenio Guimarães; Silveira, Pedro Marques da; Marchão, Robélio Leandro; Becquer, Thierry; Balbino, Luiz Carlos (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this work was to characterize soil fauna groups and to evaluate the effects of cover crops under no-tillage system, in a Cerrado Oxisol, in two evaluation periods. The cover crops: Crotalaria juncea, Cajanus cajan, Stylosanthes guianensis, Brachiaria brizantha, Brachiaria brizantha/Zea mays association, Pennisetum glaucum, Panicum maximum and Sorghum bicolor were cultivated from November to April of each year. Common bean was sown every September under centre pivot irrigation. The area of each plot was 60 m2. Soil monoliths (25x25 cm) were taken randomly from each plot, at 0–10 cm and 10–20 cm dephs, in April and September, 2005, and macrofauna was hand sorted. Identified groups in decreasing order of total density are: Formicidae, Oligochaeta, Dermaptera, Coleoptera, Hemiptera, Miriapoda, Isoptera, Araneae, Lepidoptera, Blattodea and Diptera larvae. Crotalaria juncea showed the highest macrofauna density, followed by B. brizantha, B. brizantha/Zea mays association, Sorghum bicolor, Stylosanthes guianensis, Cajanus cajans, Pennisetum. glaucum, Panicum maximum. The use of cover species in no-tillage system, associated with irrigation, promotes soil colonization by macrofauna.